Price coordination in two-sided markets: Competition in the TV industry - Hans Jarle Kind; Tore Nilssen; Lars Sørgard (University of Oslo, Department of Economics, 2010)
Under the current market structure in the TV industry advertising prices are typically set by TV channels while viewer prices are set by distributors (e.g., cable operators). The latter implies that the distributors partly internalize the competition between the TV channels, since they take into account the fact that a lower viewer price at one channel will reduce the willingness to pay for rival channels. We find that a shift to a market structure where advertising prices as well as viewer prices are set competitively by the TV channels might increase joint industry profits. The reason is that this market structure, in contrast to the one we observe today, directly addresses the two-sidedness of the market. We also show that this is to the benefit of the viewers.
Keywords: L13; L22; L82; 330; Two-sided markets; advertising; media economics; Fernsehen; Fernsehprogramm; Fernsehwerbung; Willingness to pay; Marktsegmentierung